Improving Patient Safety through Nursing Handover Quality in Hospital Inpatient Wards: A PLS-SEM Analysis - Kayla Putri Legawa; Ferdi Antonio (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
Nursing management concept often prioritizes standard operating procedures over the psychological and interpersonal dynamics that are crucial in high-pressure workplaces. However, the problem that generally arises is at the concept execution stage. This study examines the relation of non-structural elements, particularly in patient safety performance, through individual resilience and leadership. With 201 nurses in the hospital purposively being studied and the results being analyzed through the Partial Least Squares Structural Equation Modeling (PLS-SEM), the results found that nurse resilience, safety climate, and leadership are the determinants of reinforcing team coordination (R² = 0.534) and organizational citizenship behavior (R² = 0.559). Care coordination (β= 0.332, p < 0.001) and organizational citizenship behavior (β= 0.518, p<0.001) have significant impacts on handover quality, with OCB showing stronger impacts. The results suggest that the handover quality is the prominent variable that determines the quality of patient safety (β = 0.618; p < 0.001), which accounts for about 38% of the variation. Remuneration based on performance shows strengthening moderating effects (β= 0.111, p = 0.022), serving as an enabler that enhances the influence of care coordination on handover quality.